ANALISIS PENGARUH DIMENSI KEPERCAYAAN (MULTI DIMENSIONAL TRUST) DAN RISIKO YANG DIRASAKAN (PERCEIVED RISK) DENGAN MODEL MODIFIKASI UTAUT-LUO TERHADAP PENGGUNAAN LAYANAN INTERNET BANKING DI INDONESIA - Melya Yosita; Refi Rifaldi Windya Giri (JURNAL LENTERA BISNIS, 2016)
Indonesia got the fourth rank in Asia Pacific for having the biggest internet users on 2014 and shows the significance growth every years supported with the internet penetration rate. But this condition doesn’t supported by the number of internet banking user in Indonesia. If compared with Malaysia which has the number of internet user less than Indonesia but shows the greater number on internet banking user. The purpose of the study is to determine the effect of multi-dimensional trust (disposition of trust, structural assurance and trust belief), perceived risk and Luo UTAUT modification model on behavioral intention toward using internet banking service in Indonesia. Data collected using quota sampling method and 450 respondents are gathered from three different areas in Indonesia (Sumatera, Jawa and East Indonesia). Structural Equation Modeling (SEM) with AMOS version 21 software is used as data analysis technique. Results from this research shows that trust belief as the key variable to determine individual for using internet banking service. Keywords : Internet Banking, Trust, Perceived Risk, AMOS, Modified UTAUT